2020
DOI: 10.1021/acs.energyfuels.9b03975
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Evaluation of the Fate of Phosphorus in Fluidized Bed Combustion of Biomass and Sewage Sludge

Abstract: Comprehensive knowledge concerning the behavior of phosphorus (P) during combustion is necessary to enable more efficient recovery of P from combustion ashes for agricultural purposes. To this end, parameters that influence the distribution and speciation of P in combustion ashes are important because they may influence which ash fractions are suitable for P recovery. This study aims to determine the fate of P as a result of fuel ash composition and chemical association in the fuel during fluidized bed combust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 48 publications
(119 reference statements)
0
4
0
Order By: Relevance
“…Previous studies have further shown that by adding K to the SS fuel mixture, plant-available phosphates in the form of K-whitlockites can be formed . Recently published research about co-combustion of SS with K-rich fuels suggests that K-phosphates are formed to a larger extent at higher temperatures of 1100–1200 °C compared to 800 °C. , However, thermodynamic equilibrium calculations (TECs) for the co-combustion of SS and K-rich agricultural fuels indicate that the formation of K-bearing phosphates is thermodynamically favored at lower temperatures relevant for fluidized bed combustion . There are also new TEC databases with enhanced applicability in P-rich systems that need to be assessed and compared to experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have further shown that by adding K to the SS fuel mixture, plant-available phosphates in the form of K-whitlockites can be formed . Recently published research about co-combustion of SS with K-rich fuels suggests that K-phosphates are formed to a larger extent at higher temperatures of 1100–1200 °C compared to 800 °C. , However, thermodynamic equilibrium calculations (TECs) for the co-combustion of SS and K-rich agricultural fuels indicate that the formation of K-bearing phosphates is thermodynamically favored at lower temperatures relevant for fluidized bed combustion . There are also new TEC databases with enhanced applicability in P-rich systems that need to be assessed and compared to experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…The association of phosphorus in biomass ash and char has been studied by numerous researchers. However, Öhman (refs , , , , , , , , , , , , , , , ), Boström (refs , , , , , , , , , , , , , ), Skoglund (refs , , , , , , , , , , , , , , ), and their co-workers have performed considerable work within the field and should be acknowledged for investigating the fate of phosphorus in various types of biomass, and the combustion characteristics of several phosphorus-rich biomass types. In this section, a conceptual model developed by them, to aid the understanding of phosphorus transformation(s) in biomass ash, will first be presented.…”
Section: Transformation Of Phosphorus In Biomass Conversionmentioning
confidence: 99%
“…It is stated that volatile K can be captured by aluminum silicates. Furthermore, crystalline phases containing potassium and phosphorus have been identified in ash from phosphorous-rich DSS such as sewage sludge, which are mainly in the form of CaK 2 P 2 O 7 , MgKPO 4 , and CaKPO 4 [20,25,26].…”
Section: Chemical Fractionationmentioning
confidence: 99%